A new orbit for comet C/1819 N1 (Great comet of 1819) - Branham, Richard Lacy (2017)
A new orbit is calculated for Comet C/1819 N1 (Great Comet of 1819) to replace Peck’s parabolic orbit of 1906. The orbit is based upon 402 observations in right ascension and 294 in declination, made between July and October of 1819. The orbit is a high eccentricity ellipse.